2013
DOI: 10.5539/jas.v5n5p176
|View full text |Cite
|
Sign up to set email alerts
|

Definition of Zones With Different Levels of Productivity Within an Agricultural Field Using Fuzzy Modeling

Abstract: Zoning of agricultural fields is an important task for utilization of precision farming technology. A method based on fuzzy indicator model theory for definition of zones with different levels of productivity is considered. Fuzzy indicator model for identification of zones with different levels of productivity is based on two general types of fuzzy indicators: the individual fuzzy indicator (IFI) type and the combined fuzzy indicator (CFI) type. IFIs are defined as a number in the range from 0 to 1, which refl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…In this method, experts can define their own opinions about the significance of parameters determining productivity in numerical forms, or as linguistic propositions. It should be noted that with this developed method (Kurtener et al, 2011(Kurtener et al, , 2013 it is postulated that at within an agricultural field all zones with the different levels of productivity exist, but with different grades. The value of the grade is estimated with fuzzy indicators, which rang from zero to one.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…In this method, experts can define their own opinions about the significance of parameters determining productivity in numerical forms, or as linguistic propositions. It should be noted that with this developed method (Kurtener et al, 2011(Kurtener et al, , 2013 it is postulated that at within an agricultural field all zones with the different levels of productivity exist, but with different grades. The value of the grade is estimated with fuzzy indicators, which rang from zero to one.…”
Section: Methodsmentioning
confidence: 99%
“…In this case, the expert opinions are formulated as several alternatives, and an optimal alternative is defined using the tool for multi-attributive decision-making. A chart illustrating how the combination of the developed method (Kurtener et al, 2011(Kurtener et al, , 2013) with a tool for multi-attributive decision-making could work is shown in figure 1.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations